Nitric oxide regulates photosynthesis and the capacity of the antioxidant system under water deficit and rehydration in Lolium multiflorum/Festuca arundinacea introgression forms - Perlikowski, Dawid; Lechowicz, Katarzyna; Blicharz, Sara; Arasimowicz-Jelonek, Magdalena; Czapiewska, Adrianna; Pawłowicz, Izabela; Kosmala, Arkadiusz (Frontiers in Plant Science, 2025)
Although numerous studies have already indicated the important roles of nitric oxide (NO) in adaptations of different plant species, including forage grasses, to water deficit conditions, the precise mechanisms of its action have not been fully recognized. Thus, the purpose of this work was to identify the key physiological traits and understand their relations with plant response to soil water deficit and subsequent rewatering under modulated NO content in Lolium multiflorum/Festuca arundinacea introgression forms distinct in the levels of drought tolerance. To reduce NO content in plant cells, NO scavenger, 2-phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (PTIO), was used. The obtained results clearly indicated a higher photosynthetic capacity of the plants with a decreased NO content on the 12th day of water deficit (12% of soil water content), which was manifested by a higher CO2 assimilation level. This phenomenon was associated with delayed stomata closure observed under these simulated conditions and resulted in a higher level of transpiration. Moreover, the plants with a lower NO content were characterized by a significantly higher water uptake in the early stages of water deficit progression, which could disturb their drought tolerance. Scavenging of NO also resulted in elevated H2O2 content, decreased activity of ascorbate peroxidase on the 14th day of water deficit (5% of soil water content) and subsequent rewatering, and a higher level of lipid peroxidation, which could impact cellular homeostasis of the analyzed introgression forms.